Pemanfaatan Web Inkubator Bisnis Sebagai Media Pendampingan dan Promosi UMKM dalam Meningkatkan Akses Pasar Digital - Marselina Marselina; Ukhti Ciptawaty; Tri Joko Prasetyo; Sudrajat Sudrajat (Institut Nalanda, 2026)
This community service article discusses the use of a business incubator website as a medium for mentoring and promoting Micro, Small, and Medium Enterprises (MSMEs). The platform provides an integrated ecosystem consisting of incubation programs, digital branding assistance, investor networking, a learning center, and an exclusive marketplace page for each MSME member. These features make the platform relevant as a tool for strengthening MSME digital capacity through community engagement activities.The service activity was designed using a participatory mentoring approach involving problem identification, training on website utilization, content assistance for MSME profiles, and evaluation of platform use. Referring to previous community service practices, incubation-based mentoring can improve entrepreneurial understanding, strengthen business capacity, and support sustainable business development when supported by structured guidance and evaluation.The results show that the incubator website helps MSME partners present business profiles, business background, product information, location, contact details, and online ordering information in a more systematic way. The existence of a dedicated digital page for each enterprise strengthens visibility, supports branding, and expands market communication channels. Therefore, the business incubator website can be positioned as an effective community service instrument for improving MSME digital promotion and market access.